Changes in total serum bilirubin during phototherapy in late preterm and term infants with non-haemolytic hyperbilirubinemia. (April 2019) - Dani, Carlo; Becciani, Sabrina; Pratesi, Simone
Abstract: Background: There is no standardized method for total serum bilirubin (TSB) monitoring during phototherapy for neonatal hyperbilirubinemia and national guidelines give heterogeneous indications. Aim: To assess the hypothesis that TSB values do not exceed exsanguino-transfusion (EXT) threshold during phototherapy and that it is possible to decrease its monitoring frequency in jaundiced infants. Study design: We carried out a prospective observational study in which changes in TSB during phototherapy for non-haemolytic hyperbilirubinemia were recorded in a cohort of late preterm and term infants. TSB values after 6, 12, 18, and 24 h of phototherapy were compared to the EXT threshold matched to infants' gestational and postnatal age according to the specific nomogram of the Italian Society of Neonatology guidelines. Results: We studied 105 infants who started phototherapy at a mean age of 89 ± 37 h when mean TSB was 17.1 ± 2.5 mg/dL. We found that TSB decreased during phototherapy and the difference between mean TSB and EXT threshold progressively increased during phototherapy; TSB exceeded EXT threshold in none of our patients (0%). Conclusions: Our study demonstrates that differences between mean TSB and EXT threshold increased during phototherapy in late preterm and term infants with non-haemolytic hyperbilirubinemia; in none of our patients TSB exceeded EXT threshold. Our findings support the possibility of safely decreasing TSB monitoring during phototherapy, thus limiting noxious painful stimuli in neonates. Highlights: Differences between mean TSB and EXT threshold increased during phototherapy in late preterm and term infants with hyperbilirubinemia. In none of our patients TSB exceeded EXT threshold. It is possible to decrease TSB monitoring during phototherapy, limiting noxious painful stimuli in neonates.